Learning from rare events: An analysis of ValuJet Flight 592 and Swissair Flight SR 111 crashes. (February 2019) - Grigoriou, Konstantinos; Labib, Ashraf; Hadleigh-Dunn, Sara
Abstract: Why do organisations need to learn from prior failures in this uncertain and complex environment? How can they learn from prior failures? This paper aims to answer the above questions using the relevant literature and by analysing two cases from the aviation industry. To achieve this, Fault Tree Analyses and Reliability Block Diagram will be applied to ValuJet Flight 592 and Swissair Flight SR111 crashes to identify their root causes and discuss the lessons learned or not learned. Thus, learning from failures using advanced techniques do not only indicates the root causes of the disaster but increase the knowledge of the organisation as they can identify the gaps in their system and learn from them. Highlights: Employ a hybrid of techniques to detect the causal factors. Analyse the concept of learning from failures. Provide justification for using the chosen techniques. Provide holistic approach to the investigation of failures.